Structural biology and thermodynamics of GluD receptors. (15th June 2021) - Chin, Alfred C.; Lau, Albert Y.
Abstract: Glutamate delta (GluD) receptors are a functionally enigmatic subfamily of ionotropic glutamate receptors. Despite sharing similar sequences and structures with AMPA, NMDA, and kainate receptors, GluD receptors do not bind glutamate nor function as ligand-gated ion channels. Binding d -serine and engaging in transsynaptic protein-protein interactions, GluD receptors are thought to undergo complex conformational rearrangements for non-ionotropic signaling that regulates synaptic plasticity. Recent structural, biochemical, and computational studies have elucidated multiple conformational and thermodynamic factors governing the unique properties of GluD receptors. Here, we review advances in biophysical insights into GluD receptors and discuss the structural thermodynamic relationships that underpin their neurobiological functions. This article is part of the Neuropharmacology Special Issue on 'Glutamate Receptors – Orphan iGluRs'. Highlights: GluD receptors form transsynaptic complexes and mediate non-ionotropic signaling. GluD LBD dynamics are structurally characterized but remain functionally enigmatic. Molecular simulations provide thermodynamic insights into GluD LBDs.